2014
DOI: 10.3920/wmj2013.1677
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the rapid acoustic screening of deoxynivalenol in wheat grains

Abstract: Deoxynivalenol (DON) is a natural and ubiquitous toxic metabolite produced by filamentous fungi of the genus Fusarium. Approximately one quarter of the world's food crops (mainly cereals) are affected by mycotoxins such as DON. A rapid and non-destructive method to evaluate the quality and safety of grains is therefore required to eliminate these toxins from the food chain. The first portable acoustic device that predicts the concentration of DON in cereal grains has been developed using a broadband capacitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Results indicated that as microbiological contamination of nuts increased, the amplitude of the acoustic signal penetrating the nut sample decreased. The obtained results are in agreement with previous studies in which a strong dependence between DON and the content of scabby kernels in wheat matrix was found by Juodeikiene et al (2008Juodeikiene et al ( , 2014b and Tutelyan (2004). The results of the fungal invasion are that the attacked grains shrivel (become scabby in the case of wheat) and become more porous.…”
Section: The Application Of the Acoustic Screening Technique For The supporting
confidence: 92%
See 1 more Smart Citation
“…Results indicated that as microbiological contamination of nuts increased, the amplitude of the acoustic signal penetrating the nut sample decreased. The obtained results are in agreement with previous studies in which a strong dependence between DON and the content of scabby kernels in wheat matrix was found by Juodeikiene et al (2008Juodeikiene et al ( , 2014b and Tutelyan (2004). The results of the fungal invasion are that the attacked grains shrivel (become scabby in the case of wheat) and become more porous.…”
Section: The Application Of the Acoustic Screening Technique For The supporting
confidence: 92%
“…Samples of the corn grain, corn grain model system, and different nuts model systems were screened using a recently developed portable acoustic spectrometer (Figure 1) with penetration (Juodeikiene et al, 2014b).…”
Section: Acoustic Techniquementioning
confidence: 99%
“…In addition to the chemical and immunochemical methods for DON, 3‐Ac‐DON, 15‐Ac‐DON and DON‐3‐glucoside, there exist non‐invasive screening methods based on the spectroscopic characteristics of the analytes or on the acoustic characteristics of DON‐contaminated grain kernels. (Kos et al., ; Juodeikiene et al., , ; Liu et al., ; Fox and Manley, ). Another alternative screening method that can detect DON contamination of cereal grains with high sample throughput is the electronic nose (Campagnoli et al., ; Lippolis et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In their paper 'Recent advances in the rapid acoustic screening of deoxynivalenol in wheat grains' , Juodeikiene et al (2014) report on the first portable acoustic device predicting the concentration of DON in cereal grains, which has been developed using a broadband capacitive ultrasonic transducer. This paper describes an acoustic method optimised for the rapid prediction of DON in wheat.…”
Section: Foreword: Rapid Methods For Mycotoxin Detectionmentioning
confidence: 99%